2012
DOI: 10.1016/j.drugalcdep.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in trajectories of heavy drinking and regular marijuana use from ages 13 to 24 among African-American and White males

Abstract: Background Although there are significant differences in prevalence of substance use between African-American and White adolescents, few studies have examined racial differences in developmental patterns of substance use, especially during the important developmental transition from adolescence to young adulthood. This study examines racial differences in trajectories of heavy drinking and regular marijuana use from adolescence into young adulthood. Methods A community-based sample of non-Hispanic African-Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 26 publications
6
53
0
Order By: Relevance
“…This sample reflects an understudied population with particular higher risk for both cannabis use and mental health problems (Finlay et al, 2012). We used a three-wave cross-lag panel model that allowed us to test reciprocal, transactional relationships between cannabis use and depressive symptoms at three time points from adolescence to early adulthood.…”
mentioning
confidence: 99%
“…This sample reflects an understudied population with particular higher risk for both cannabis use and mental health problems (Finlay et al, 2012). We used a three-wave cross-lag panel model that allowed us to test reciprocal, transactional relationships between cannabis use and depressive symptoms at three time points from adolescence to early adulthood.…”
mentioning
confidence: 99%
“…Moreover, Black youths are also more likely to drink to escape or avoid emotional distress, whereas White youths are likely to drink to enhance positive affect (Cooper et al, 2008); thereby, providing support that Black youths who do use substances tend to do so as a coping response. In addition, Black and White differences in substance use tend to converge in later adulthood (Finlay et al, 2012;Herd, 1990; SAMHSA, Center for Behavioral Health Statistics and Quality, 2011). Thus, identifying factors of risk during adolescence and young adulthood may inform intervention and prevention efforts to reduce later adverse consequences of drug use behaviors.…”
Section: Introductionmentioning
confidence: 96%
“…On the one hand, compared to other racial/ethnic groups, Blacks are disadvantaged in terms of discrimination, financial hardships, exposure to violence, and access to quality health care and other social services (U.S. Department of Health and Human Services, 2001). On the other hand, both community and national-level studies have found that Blacks tend to report substantially lower rates of substance use than their White counterparts (Boardman & Alexander, 2011;Finlay, White, Mun, Cronley, & Lee, 2012; Substance Abuse and Mental Health Services Administration [SAMHSA], 2012). Given this apparent inconsistency, there is a need to closely examine the association between stress and substance use among Black youths by exploring how specific types of stressors contribute to the variability in their substance use and whether the associations of stress exposure and drug use are indeed different for Black and White youths.…”
Section: Introductionmentioning
confidence: 97%
“…Our focus on African Americans is critical given that this group is exposed to multiple and unique risk factors (Chen & Jacobson, 2012;Finlay, White, Mun, Cronley, & Lee, 2012;Saxe et al, 2001;Wu, Temple, Shokar, Nguyen-Oghalai, & Grady, 2010), is among those least likely to receive treatment for substance use disorders (Alegria, Carson, Goncalves, & Keefe, 2011;Wells, Klap, Koike, & Sherbourne, 2001), and suffers the highest rates of morbidities associated with drug use (Gil, Wagner, & Tubman, 2004;Green et al, 2010;Zapolski et al, 2014). Moreover, while comparing disadvantaged females to females from higher SES and African Americans to Whites is useful, these approaches provide limited information for designing tailored interventions.…”
Section: Introductionmentioning
confidence: 96%